La configuración de proyectos de vida desarrolladores: Un programa para su atención psicopedagógica - Pérez Gamboa, Alfredo Javier; García Acevedo, Yanetsy; García Batán, Jorge; Raga Aguilar, Lis Marianne (Universidad de Costa Rica, 2023)
The objective of the research was to promote the configuration of developing life projects, through the implementation of a program for the psychopedagogical treatment of it. For this purpose, new concepts are proposed that facilitate the development of university educational counseling and guidance. A qualitative methodology is used with an action research design and the case study as a strategy for the study of implementation. It was carried out at the University of Camagüey, with a sample of thirteen students and eight professors, between November 2019 and March 2021. The main results point towards an adequate integration of the educational counseling and guidance to the managment of the university training process from the development of the proposed concepts and their application in praxis; the psychopedagogical treatment of the life project dynamized its configuration with a developmental character, since important transformations are verified with respect to the initial state. The implementation of the program was marked by the conditions of the COVID-19 pandemic, although it was positively evaluated for its formal quality, acceptance by the participants, and contextual adaptation. The results demonstrate the importance of managing the life project as a category that regulates the university training process, the opportunities and advantages offered by not limiting its treatment to the professional sphere, as well as suggest continuing the process of deepening the relationship between the processes with guidance and counseling purposes.